Faktor-Faktor Yang Memengaruhi Nilai Perusahaan Dengan Capital Structure Sebagai Variabel Mediasi - Eji Fajilet, Linda Santioso (Jurnal Paradigma Akuntansi, 2019)
The purpose of this research is to examine empirical evidence the influence of firm size, asset growth and profitability toward firm value as capital structure mediating variable on manufacturing companies in the Indonesian Stock Exchange in the period of 2015-2017.This research uses a sample of 66 companies that selected using purposive sampling method.Eviews version 9.0 is used to processed data for analysis and hypothesis test. The result of this research shows that firm sizehas positive effect to capital structure. Asset growth and profitablity have no effect to capital structure. Capital structure able to mediate the effect of firm size to firm value. Capital structure unable to mediate the effect of asset growth and profitability to firm value. Capital structure has positive effect to firm value